Household Drinking Water Source, Treatment, Storage, and Weather Conditions in Relation to Drinking Water Quality in Klaten District, Indonesia - Desy Vidi Kurniasari; Arsita Eka Prasetyawati; Hafi Nurinasari; Siti Khoiriyah; Cynthia Permata Sari (Masters Program in Public Health, 2026)
Background: Safe drinking water remains a major public health challenge in Indonesia, where contamination continues to contribute to diarrheal disease burden. Household drinking water quality surveillance coverage in Klaten District remains far below the national target. This study analyzed the association between water source protection, household water treatment, water storage conditions, and climatic factors with household drinking water quality in Klaten District. Subjects and Methods: A cross-sectional study was conducted among 390 households from 26 subdistricts in Klaten District, selected via equal-allocation subsampling from the 2025 National Household Drinking Water Quality Surveillance Program (SKAMRT) using two-stage cluster sampling (15 households/subdistrict). Drinking water quality was classified as safe or unsafe based on five parameters (E. coli, Total Dissolved Solids, pH, nitrate, nitrite) per Ministry of Health Regulation No. 2/2023. Associations were assessed using Chi-square and Fisher's exact tests, followed by multiple logistic regression with backward stepwise elimination (α = 0.05). Results: Of 390 households, 202 (51.8%) had unsafe drinking water. Unprotected water sources were the only significant determinant of unsafe water quality (Adjusted OR = 1.61; 95% CI: 1.05–2.47; p = 0.029). Water treatment, storage type, and weather conditions showed no statistically significant association. Spatial analysis identified five subdistricts with very high risk (>80% non-compliant): Polanharjo (93.3%), Wonosari (86.7%), Bayat, Tulung, and Klaten Tengah (80.0% each). Model calibration was adequate (Hosmer-Lemeshow p = 0.741). Conclusion: Unprotected water sources represent an independent determinant of unsafe household drinking water quality in Klaten District. Interventions should prioritize water source protection, household water safety education, and expansion of SKAMRT surveillance coverage to support SDGs 6.1 achievement by 2030.